A study on ethics practices of construction industry in Wilayah Persekutuan - Airinah Nazli, Aziz (2016)
Ethics is a crucial factor to maintain good reputation of construction industry and generate economic growth in Malaysia. According to Weymes (2005), the growing demand of good ethics practices in any forms of business has been highlighted numerously. Increasing numbers of ethical issues shows the lack of ethics practices in construction industry of this country. Construction industry has been one of the contributors to the economic growth of Malaysia and this industry should be at the best reputation to maintain as the top contributor. Hence, the purpose of this research is to provide the industry with effective methods in encountering ethical issues. Questionnaire survey is used to obtain data from 291 respondents which are contractors in Wilayah Persekutuan. Thus, the data analysis provided that economic downturn, national objectives, leadership and non-transparent of selection process are the causes to ethical issues. Effective methods that are the best to implement is Code of Conduct and early education. To conclude, ethics practices should be implemented in construction industry because this industry is the main contributor to economic development of this country.